Acute effect of zoledronic acid infusion on atrial fibrillation development in patients with osteoporosis - ÇİNÇİN, AHMET ALTUĞ; KEPEZ, ALPER; ERDOĞAN, OKAN (AVES, 2015)
Objective: There is ongoing controversy related to the relationship between bisphosphonates and atrial fibrillation (AF). Our aim in this study was to evaluate the potential acute effect of zoledronic acid (ZA) infusion on AF development by using 24-hour Holter recordings. Methods: The study was designed to be a self-controlled case series study, and 33 consecutive patients with osteoporosis (29 females, age: 62.3 +/- 9.0 years) who were scheduled to receive ZA infusion constituted the study population. Patients underwent 24-hour Holter rhythm recordings at two different times; the first one was 48 hours before the planned ZA infusion, and the second one was on the morning of the infusion day. Heart rate, frequency and type of arrhythmias, as well as heart rate variability (HRV) from the two recordings were compared. Results: There were no episodes of AF greater than 30 sec in any of the 24-hour Holter recordings obtained before and on the day of drug infusion. Holter recordings before drug infusion showed that only 1 patient had an atrial run of 3 beats long. Holter recordings obtained on the day of drug infusion revealed that 5 patients (15.2%) had atrial runs with lengths ranging between 3 and 12 beats (p=0.046). Regarding HRV variables, SDANN values were found to be significantly depressed on the day of ZA infusion (113.6 +/- 26.9 vs. 98.2 +/- 29.9, p=0.007). Conclusion: None of the patients developed AF during or early after ZA infusion. However, there was an increase in atrial ectopy in some patients, which might be due to alterations in cardiac autonomic activity.
Keywords: osteoporosis; zoledronic acid; atrial fibrillation; 24-hour Holter recording; SAFETY; BISPHOSPHONATES; ALENDRONATE; FRACTURES